Exact solution of the Izergin-Korepin Gaudin model with periodic and open boundaries - Xiaotian Xu, Pei Sun, Xin Zhang, Junpeng Cao, Tao Yang (SciPost Physics Core)
We study the Izergin-Korepin Gaudin models with both periodic and open integrable boundary conditions, which describe quantum systems exhibiting novel long-range interactions. Using the Bethe Ansatz approach, we derive the eigenvalues of the Gaudin operators and the corresponding Bethe Ansatz equations.